DAYA SAING KOPERASI, USAHA KECIL MIKRO (KUKM) AGROBISNIS MENGHADAPI PASAR INTRA ASEAN: KASUS KUKM ACEH TENGAH, PROVINSI ACEH - Hasan, Ishak (JURNAL KEBANGSAAN, 2016)
This study aim to analyse cooperative, small and medium business enterprises (KUMKM) on base of the Agro-bussines facing of Competitiveness Intra Asean Market in Central of Aceh Regency. Population in research is all KUMKM under develop on Board of Cooperative, Industry and Commerce (Diskopindag) of Central Aceh Regency being based on agro-bussines. Sampel was done of the trained and developed about management of is effort; administration, accountancy, marketing and exploiting of various facility of is inclusive of information technology that is as much 80 KUMKM. Analyse conducted by regression of variable supporting power of KUMKM. The study result show that variables identified in model to progress of effort KUMKM equal to 0,66%. While if seen from level of influence relative minimize, that is only equal to 0,44%. Its Small cause is the influence possibility of progress variables of effort, with the indicator only mount the advantage and satisfaction in trying to represent the small shares from progress variables of is effort very macro. But that way result of this study represent the step of early good in comprehending by riel is condition faced by KUMKM in Central Aceh Regency. To be obtained by a more result utilize the importance of planning and better future policy needed by research coverage of inclusive of indicator amount as well as amount of sampel of larger ones again. Other cause of this research possibility not make classified of stratified random sampling. Because in the fact KUMKM are differed. The difference of the aspect; a) scale of business, b) market share, c) capital, d) labor force, and the others.. Keyword : CSMES, Agrobisnis, AEC